ANALISIS KESALAHAN SISWA SMP KELAS IX PADA MATERI BANGUN RUANG SISI DATAR SAAT MENYELESAIKAN SOAL BERPIKIR KRITIS - Sidik, Muhammad Jafar; Hendriana, Heris; Sariningsih, Ratna (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This research belongs to qualitative descriptive research which attempts to describe the analysis of student error in solving the problem of critical thinking mathematics on the material of building flat side space. Subject in this research is SMPN 5 Cimahi students of class IX-B which in this case student have studied material of building flat side space. The instruments used consisted of tests of critical mathematical thinking skills and student interviews. The results showed that the location of the mistakes made by the students is a mistake of concepts, error translation and strategy error. Factors that cause the error because they do not understand simple concepts, do not know the purpose of the problem, can not translate the problem into the mathematical sentence, can not finish the mathematical sentence.